1985
DOI: 10.1007/bf02424492
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of resistance of Israeli wild emmer wheat to pathogens I. Predictive method by ecology and allozyme genotypes for powdery mildew and leaf rust

Abstract: The association of ecological factors and allozyme markers with genotypes of tetraploid wild emmer wheat, Triticum dicoccoides, varying in resistance to four cultures of the pathogen Ervsiphe graminis tritici, and to one culture of Puccinia recondita tritici, which incite the diseases powdery mildew and leaf rust respectively, were explored theoretically and practically. The study involved 233 accessions comprising 10 populations representing the ecological range of 7". diococcoides in Israel. Our results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Enzyme marker genes are ideal candidates for such a study as we have shown already in our own work on powdery mildew in wild barley (Nevo et al, 1984a), and on powdery mildew, leaf rust, stripe rust and agronomic elite characters in wild emmer (Nevo et al, 1984b(Nevo et al, , 1985a. In the present study we have shown that protein percentage, kernel weight and protein weight (--protein percentage • kernel weight) in wild emmer are associated with allozyme genotype markers singly or in combinations.…”
Section: Prediction Of Protein Content and Seed Characters By Allozymmentioning
confidence: 95%
“…Enzyme marker genes are ideal candidates for such a study as we have shown already in our own work on powdery mildew in wild barley (Nevo et al, 1984a), and on powdery mildew, leaf rust, stripe rust and agronomic elite characters in wild emmer (Nevo et al, 1984b(Nevo et al, , 1985a. In the present study we have shown that protein percentage, kernel weight and protein weight (--protein percentage • kernel weight) in wild emmer are associated with allozyme genotype markers singly or in combinations.…”
Section: Prediction Of Protein Content and Seed Characters By Allozymmentioning
confidence: 95%
“…Wild emmer wheat is an important genetic resource that could be exploited in breeding for resistance to a broad range of diseases, pests, and for tolerance to poor soil and climatic factors (Nevo 1983(Nevo , 1989(Nevo , 1995. Among many agriculturally important characteristics already found in T. dicoccoides is its resistance to stripe rust (Gerechter-Amitai and Stubbs 1970;Nevo et al 1986;Fahima et al 1998), stem rust (Nevo et al 1991), and powdery mildew (Nevo et al 1985). Wild emmer wheat contains rich and variable genetic resources that will play a major role in future wheat improvement (Nevo 1983(Nevo ,1989(Nevo , 1995.…”
Section: Org]mentioning
confidence: 99%
“…Consequently, such associations are expected to occur more frequently in clones than in sexually reproducing germplasm, and in inbreeding populations more frequently than in outbreeding populations. Indeed, several recently reported examples of genetic marker-facilitated utilization involve highly autogamous or clonally propagated crops (Nevo et al 1984(Nevo et al , 1985Weeden et al 1984;Zhang and Tang 1987;Martin et al 1991). Nevertheless, genetic markers are not effective in this role in every clonal or inbreeding species (e.g., Burdon and Jarosz 1989).…”
Section: Exploiting Associations Among Traits Of Interest and Geneticmentioning
confidence: 99%